(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: CCTV cameras are widely used to monitor traffic, but they often come with limitations that still force officials to check traffic flow manually. In this work, we introduce a simple and automatic method to measure traffic volume and vehicle speed by analyzing pixel patterns from CCTV video. Our approach begins by marking vertical and horizontal reference lines on each lane and collecting pixel information from these lines in every video frame. When a vehicle crosses these lines, the change in pixel brightness clearly reveals its movement. By studying these brightness changes, we can automatically detect vehicles and calculate key traffic parameters accurately.